2022
DOI: 10.3390/foods11030315
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Successful Application of Vibrational Spectroscopy Techniques to Quantify Nutraceuticals in Fruits and Plants

Abstract: Vibrational spectroscopy techniques are the most used techniques in the routine analysis of foods. This technique is widely utilised to measure and monitor the proximate chemical composition (e.g., protein, dry matter, fat and fibre) in an array of agricultural commodities, food ingredients and products. Developments in optics, instrumentation and hardware concomitantly with data analytics, have allowed for the progress in novel applications of these technologies in the field of nutraceutical and bio compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The potential for employing spectral measurement approaches in the quality control of fruits and vegetables is growing enormously ( Escárate et al., 2022 ). The reason is that these approaches are non-destructive, fast and accurate, capable for both quantitative and qualitative analysis, thereby requiring minimal sample preparation ( Cozzolino, 2022 ). We divided non-destructive spectral measurements into two categories: (1) spectral-based approaches (FTIR, NIR, and Raman spectroscopy) and (2) imaging-based approaches (HSI), as shown in Figure 1 .…”
Section: Non-destructive Spectral Measurements For the Quality Evalua...mentioning
confidence: 99%
“…The potential for employing spectral measurement approaches in the quality control of fruits and vegetables is growing enormously ( Escárate et al., 2022 ). The reason is that these approaches are non-destructive, fast and accurate, capable for both quantitative and qualitative analysis, thereby requiring minimal sample preparation ( Cozzolino, 2022 ). We divided non-destructive spectral measurements into two categories: (1) spectral-based approaches (FTIR, NIR, and Raman spectroscopy) and (2) imaging-based approaches (HSI), as shown in Figure 1 .…”
Section: Non-destructive Spectral Measurements For the Quality Evalua...mentioning
confidence: 99%
“…Many analytical techniques have been employed for that goal, among them Raman spectroscopy [7,12]. As a matter of fact, the application of vibrational spectroscopy techniques to quantify nutraceuticals in fruits and plants has proven successful [13], and Raman spectroscopy has been used for quantitative analysis in the pharmaceutical industry [14,15]. The evolution of Raman as an extremely sensitive analytical tool was further boosted by the discovery of several other Raman phenomena, including Resonance Raman (RR), coherent anti-Stokes Raman scattering (CARS), and surface-enhanced Raman scattering (SERS) [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It could be considered a promising technology to be utilized by plant breeders as well as in a variety of industries where rapid screening of numerous samples for antioxidant and/or phenolic content is required [ 9 ]. Several studies have reported the ability of near infrared (NIR) spectroscopy which works in the spectral range 13000–4000 cm −1 , to predict, with the help of multivariate calibration methods, the presence of different bioactive compounds in tea such as catechins, caffeine, free amino acids and theaflavins [ 10 , 11 , 12 , 13 , 14 , 15 ]; this technique has been also used to discriminate different tea varieties, also in relation with the geographical origins, and to identify tea grades and tea processing degree [ 10 , 16 , 17 , 18 ]. Conversely, to the best of our knowledge, only a few studies can be found in the literature regarding the use of FTIR spectroscopy in the MIR region (spectral range 4000–400 cm −1 ) to investigate tea leaves and tea brews and to highlight differences due to processing, cultivation site and extraction methods [ 4 , 16 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%